The Study of Errors and Feedback in Second Language Acquisition (SLA) Research: Strategies used by the ELT practitioners in Bangladesh to address the errors their students make in learning English - Ali, Md Maksud (IIUC Studies, 2014)
The study of errors and feedback is one of the major issues in Second Language Acquisition (SLA) research. The research in this area is so important because it gives the English language teaching (ELT) practitioners an opportunity to have an insight in understanding the nature of learners errors and in giving feedback to learners. Following quantitative method, this paper carries out an empirical cross-sectional survey research on errors and feedback in SLA in the context of Bangladesh in order to generalize the way in which the Bangladeshi ELT practitioners view their students errors and the ways they correct the errors. DOI: http://dx.doi.org/10.3329/iiucs.v8i0.20409 IIUC Studies Vol.8 December 2011: 131-140